2016
DOI: 10.1186/s12881-016-0358-3
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the UMOD promoter is associated with end stage renal disease

Abstract: BackgroundSeveral genome-wide association studies revealed that several variants of UMOD gene were related to the estimated glomerular filtration rate (eGFR), CKD or hypertension. In this study, we investigated the association between a common variant rs13333226 in the promoter region of UMOD gene and end stage renal disease (ESRD).MethodsVariant rs13333226 of UMOD gene was genotyped by using the ABI Real time TaqMan allelic discrimination assay in a case-control study including 638 unrelated patients with ESR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Several common UMOD variants (rs12917707, rs4293393, rs11864909, rs13329952) are associated with both CKD and eGFR (Köttgen et al, 2009, 2010; Gudbjartsson et al, 2010; Pattaro et al, 2012, 2016). More recently, the higher frequency in ESRD of another common UMOD variant (rs13333226), has been confirmed in 638 Chinese patients with ESRD and 366 controls (Chen et al, 2016). Several common variants in the myosin heavy chain type II isoform A ( MYH9 ) gene have been associated with non-diabetic ESRD in African Americans (Kao et al, 2008; Kopp et al, 2008; Chambers et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Several common UMOD variants (rs12917707, rs4293393, rs11864909, rs13329952) are associated with both CKD and eGFR (Köttgen et al, 2009, 2010; Gudbjartsson et al, 2010; Pattaro et al, 2012, 2016). More recently, the higher frequency in ESRD of another common UMOD variant (rs13333226), has been confirmed in 638 Chinese patients with ESRD and 366 controls (Chen et al, 2016). Several common variants in the myosin heavy chain type II isoform A ( MYH9 ) gene have been associated with non-diabetic ESRD in African Americans (Kao et al, 2008; Kopp et al, 2008; Chambers et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Gómez et al 19 found a missense mutation p.V458L in which leucine variant was more frequent in individuals with reduced GFR as compared to healthy individuals with normal GFR. Associations of UMOD rs13333226 G allele with hypertension, CKD 20 and ESRD 26 have been reported. However, Cui et al 27 reported association of rs13333226G allele with slower decline in renal function in individuals with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The etiologies of many diseases have been attributed to SNPs, and their identification has contributed to the pathophysiology of different types of CKD [3,5]. For example, the presence of susceptibility variants in particular gene loci (e.g., the loci of UMOD and APOL1), may increase the risk of CKD and increase the possibility of end stage renal disease (ESRD) in specific populations [6,7]. Namely, APOL1 polymorphisms, which are found as homozygous recessive risk alleles in approximately 10% of the African American population, are now recognized as risk factors that increase the progression of hypertensive and glomerular kidney diseases [7].…”
Section: Introductionmentioning
confidence: 99%